2018
DOI: 10.1111/imm.13021
|View full text |Cite
|
Sign up to set email alerts
|

Jagged1‐expressing adenovirus‐infected dendritic cells induce expansion of Foxp3+ regulatory T cells and alleviate T helper type 2‐mediated allergic asthma in mice

Abstract: Summary Dendritic cells (DCs) are professional antigen‐presenting cells that play a key role in directing T‐cell responses. Regulatory T (Treg) cells possess an immunosuppressive ability to inhibit effector T‐cell responses, and Notch ligand Jagged1 (Jag1) is implicated in Treg cell differentiation. In this study, we evaluated whether bone marrow‐derived DCs genetically engineered to express Jag1 (Jag1‐DCs) would affect the maturation and function of DCs in vitro and further investigated the immunoregulatory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 53 publications
2
13
0
Order By: Relevance
“…Therefore, Notch pathway is a critical regulator of PD-1 regulation. Furthermore, the overexpression of Jag1 on DCs increased PD-L1 expression and the coculture of CD4 + T cells with these Jag1-DCs promoted Treg generation, while PD-L1 blockade partially reduced Treg expansion 28. The above findings confirmed the important role of PD-1 in the induction of Treg expansion through modulating Notch pathway.…”
Section: The Role Of Pd-1/pd-l1 Axis In Treg Development and Functionsupporting
confidence: 65%
“…Therefore, Notch pathway is a critical regulator of PD-1 regulation. Furthermore, the overexpression of Jag1 on DCs increased PD-L1 expression and the coculture of CD4 + T cells with these Jag1-DCs promoted Treg generation, while PD-L1 blockade partially reduced Treg expansion 28. The above findings confirmed the important role of PD-1 in the induction of Treg expansion through modulating Notch pathway.…”
Section: The Role Of Pd-1/pd-l1 Axis In Treg Development and Functionsupporting
confidence: 65%
“…8 Additionally, we proved that Ad-Jagged1-infected DCs enhance the generation of Foxp3 + Treg cells. 10 Herein, we further demonstrated that Ad-DLL4-infected DCs promoted the development of Th1 cells and exerted an immunotherapeutic effect by altering the Th1/Th2 cell ratio. Thus, we concluded that Notch ligand gene-modified DCs exhibited antiallergic effects through two regulatory pathways (Fig.…”
mentioning
confidence: 60%
“…The differentiation of Treg cells relies on the DC-secret IL-10 and TGF-β. To date, numerous drugs and factors have been used to induce and maintain DCs tolerogenic by enhancing their capacity to promote activation of Treg cells (33,34). Strategies for repairing T cell immune homeostasis are expected to be translated into clinical application in the treatment of in ammatory bowel disease (IBD).…”
Section: Discussionmentioning
confidence: 99%